A Modified Hepatitis B Virus Core Particle Containing Multiple Epitopes of the Plasmodium falciparum Circumsporozoite Protein Provides a Highly Immunogenic Malaria Vaccine in Preclinical Analyses in Rodent and Primate Hosts - Birkett, A. (American Society for Microbiology, 2002)
Despite extensive public health efforts, there are presently 200 to 400 million malaria infections and 1 to 2 million deaths each year due to the Plasmodium parasite. A prime target for malaria vaccine development is the circumsporozoite (CS) protein, which is expressed on the extracellular sporozoite and the intracellular hepatic stages of the parasite. Previous studies in rodent malaria models have shown that CS repeat B-cell epitopes expressed in a recombinant hepatitis B virus core (HBc) protein can elicit protective immunity. To design a vaccine for human use, a series of recombinant HBc proteins containing epitopes of Plasmodium falciparum CS protein were assayed for immunogenicity in mice [A. Birkett, B. Thornton, D. Milich, G. A. Oliveira, A. Siddique, R. Nussenzweig, J. M. Calvo-Calle, and E. H. Nardin, abstract from the 50th Annual Meeting of the American Society of Tropical Medicine and Hygiene 2001, Am. J. Trop. Med. Hyg. 65(Suppl. 3):258, 2001; D. R. Milich, J. Hughes, J. Jones, M. Sallberg, and T. R. Phillips, Vaccine 20:771-788, 2001]. The present paper summarizes preclinical analyses of the optimal P. falciparum HBc vaccine candidate, termed ICC-1132, which contains T- and B-cell epitopes from the repeat region and a universal T-cell epitope from the C terminus of the CS protein. The vaccine was highly immunogenic in mice and in Macaca fascicularis (cynomolgus) monkeys. When formulated in adjuvants suitable for human use, the vaccine elicited antisporozoite antibody titers that were logs higher than those obtained in previous studies. Human malaria-specific CD4(+)-T-cell clones and T cells of ICC-1132-immunized mice specifically recognized malaria T-cell epitopes contained in the vaccine. In addition to inducing strong malaria-specific immune responses in naïve hosts, ICC-1132 elicited potent anamnestic antibody responses in mice primed with P. falciparum sporozoites, suggesting potential efficacy in enhancing the sporozoite-primed immune responses of individuals living in areas where malaria is endemic.